Perceptions of Material Wealth in Buddhist Economics (Rupandehi Campus Journal, 2025)
This article explores the perception of material wealth and its significance in human life within the framework of Buddhist economics. Buddhist economics is a philosophy cantered on economic well-being, emphasizing happiness, peace, and stability achieved through the regulation of desires, selfless service, and right livelihood. Also referred to as middle path economics, it advocates for the avoidance of harm to oneself and others. The research synthesizes diverse sources, encompassing articles, journals, books, and Buddhist literature, to offer a comprehensive analysis. Employing a qualitative research methodology, the study employs explanatory and exploratory approaches, with particular emphasis on content analysis. The findings of the study indicate that, in the context of Buddhist economics, material wealth is perceived as a means rather than an end in itself. It is recognized as a valuable resource that, when acquired and employed conscientiously, can yield positive outcomes not only for individuals but also for others. Ultimately, this collective well-being and happiness contribute to the broader advancement of humanity.